What Is the Cause of Apparent Preference for Sources with Chromaticity below the Blackbody Locus?. Issue 1 (2nd April 2016) - Wei, Minchen; Houser, Kevin W.
ABSTRACT: Two recent articles reported that light stimuli with chromaticity below the blackbody locus were preferred to those on or above the blackbody locus. Neither article offered an explanation for why that occurred. In this article we suggest that chromaticity may not be the sole cause of preference. The preference to the light stimuli reported in these two articles may be due to the combined effects of color rendition and chromaticity. Through simulation, we show that illuminants with chromaticity below the blackbody locus (that is, negative D uv ) are more likely to have higher scores for relative gamut (for example, Q g ) than illuminants on or above the blackbody locus, while maintaining high scores for fidelity (for example, Q f ). Future psychophysical studies that separate the effects of chromaticity and color rendition will be necessary to more fully understand preference for light stimuli.